RESEPSI KESADARAN BERBAHASA SECARA KRITIS DALAM AKTIVITAS PENULISAN FIKSI GURU DAN SISWA - Suminto Sayuti; Esti Swatika Sari; Beniati Lestyarini (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to describe the reception of critical language awareness (CLA) in the fiction writing process among senior high school (SHS) teachers and students. It was a content analysis supported by qualitative data collected through focus group discussions. The subjects were SHS teachers and students in Yogyakarta Special Territory. The data analysis in the process of interpreting meanings of their works was based on the CLA elements. The findings showed that their reception of CLA in fiction writing was reflected in both the process and the outcome. The teachers were still not optimal enough in developing methods, using media, and selecting the assessment system in the learning of fiction writing. Most of the students’ works did not reveal the awareness of the importance of language power and self-position as writers.